Rapid mitigation of carrier-induced degradation in commercial silicon solar cells. (6th July 2017) - Hallam, Brett J.; Chan, Catherine E.; Chen, Ran; Wang, Sisi; Ji, Jingjia; Mai, Ly; Abbott, Malcolm D.; Payne, David N. R.; Kim, Moonyong; Chen, Daniel; Chong, CheeMun; Wenham, Stuart R.
Abstract: We report on the progress for the understanding of carrier-induced degradation (CID) in p-type mono and multi-crystalline silicon (mc-Si) solar cells, and methods of mitigation. Defect formation is a key aspect to mitigating CID. Illuminated annealing can be used for both mono and mc-Si solar cells to reduce CID. The latest results of an 8-s UNSW advanced hydrogenation process applied to industrial p-type Czochralski PERC solar cells are shown with average efficiency enhancements of 1.1% absolute from eight different solar cell manufacturers. Results from three new industrial CID mitigation tools are presented, reducing CID to 0.8–1.1% relative, compared to 4.2% relative on control cells. Similar advanced hydrogenation processes can also be applied to multi-crystalline silicon passivated emitter with rear local contact (PERC) cells, however to date, the processes take longer and are less effective. Modifications to the firing processes can also suppress CID in multi-crystalline cells during subsequent illumination. The most stable results are achieved with a multi-stage process consisting of a second firing process at a reduced firing temperature, followed by extended illuminated annealing.